Graphite and ceramic core composite titanium alloy casting process
The surface of 1,8-naphthalene diformimide and methyl MQ silicone resin is combined by using binders of components such as yttrium oxide powder, dysprosium oxide, potassium silicate and silica sol in the preparation of ceramic cores and combining with 1,8-naphthalene diformimide and methyl MQ silicone resin The modification solves the problem of insufficient creep resistance and bending strength of ceramic cores, and improves the overall quality and production efficiency of titanium alloy castings.
Patent Information
- Application Number
- CN202411344529.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
The creep resistance and bending strength of traditional ceramic cores are poor, which affects the overall quality of titanium alloy castings.
Using graphite and ceramic core composite titanium alloy casting process, the surface-layer shell and back-layer shell are prepared on the wax mold, and the adhesives of components such as yttrium oxide powder, dysprosium oxide, potassium silicate and silica sol are used. Surface modification is carried out in combination with 1,8-naphthalene diformimide and methyl MQ silicone resin to improve the flexural strength and creep resistance of the ceramic core.
It significantly improves the bending strength and creep resistance of the ceramic core, shortens the manufacturing cycle of titanium alloy castings, and improves the overall quality and production efficiency of the castings.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloy casting, and in particular to a graphite and ceramic core composite titanium alloy casting process. Background Art
[0002] Titanium alloy has low density, high specific strength, strong corrosion resistance, and good mechanical properties at room and high temperatures. Due to its good comprehensive properties, the demand for titanium alloy castings in the aviation and aerospace fields is increasing sharply. Titanium alloy casting processes include investment casting, special sand casting and graphite casting. Among them, investment casting is widely used due to its near-net-shape process characteristics. It is generally used in medium and small products and casing products. However, at this stage, the entire process of investment casting is relatively cumbersome, and the castings have serious deformation problems, which requires the addition of thermal correction procedures. The composition is high and the casting manufacturing cycle will also increase; graphite casting process, this process was first used in casting titanium alloys. Graphite castings have the characteristics of low thermal expansion coefficient, good thermal conductivity, no erosion by molten metal, and no mold sticking. Therefore, the castings are accurate in size, not easy to deform, smooth on the surface, and improved in mechanical properties. At present, casting process designers generally use machined graphite casting, but the manufacturing cost of the entire process is high, and the inner cavity of the casting is usually an unmachined surface for complete graphite casting. The overall quality of the casting is poor, and more human resources will be needed to repair casting defects in the future.
[0003] In order to avoid the defects of castings caused by using only one titanium alloy casting process, the graphite mold formed by the machined graphite mold casting process and the ceramic core formed by the investment casting process can be combined to complement the advantages of the two titanium alloy casting processes, thereby improving the overall quality of titanium alloy castings. However, the traditional ceramic core has poor creep resistance and poor bending strength, which affects the matching of the ceramic core and the graphite mold, and also affects the overall quality of the titanium alloy casting. Therefore, improving the creep resistance and bending strength of the ceramic core is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The invention provides a graphite and ceramic core composite titanium alloy casting process, which solves the problems of poor creep resistance and poor bending strength of the ceramic core in the related art.
[0005] The technical solution of the present invention is as follows: The present invention provides a graphite and ceramic core composite titanium alloy casting process, which includes the preparation of a graphite mold, the preparation of a ceramic core, the degassing of the graphite mold, the combination of the degassed graphite mold and the ceramic core, smelting, and casting. The preparation of the ceramic core includes the following steps: S1. preparing a surface shell on a wax mold; S2, preparing a back layer shell on the surface layer shell, dewaxing, and calcining to obtain a ceramic core; In step S1, the method for preparing the surface shell mold comprises the following steps: applying a surface layer coating on the wax mold, sprinkling sand, and drying to obtain a surface shell mold; The surface coating comprises the following components in parts by weight: 23-35 parts of yttrium oxide powder and 30-50 parts of a binder; The binder includes dysprosium oxide, potassium silicate and silica sol.
[0006] As a further technical solution, the weight ratio of dysprosium oxide, potassium silicate and silica sol is 3~6:1:2.
[0007] When the weight ratio of dysprosium oxide, potassium silicate and silica sol is 3-6:1:2, the bending strength of the ceramic core can be further improved.
[0008] As a further technical solution, the yttrium oxide powder is a modified yttrium oxide powder, and the raw materials of the modified yttrium oxide powder include yttrium oxide powder and 1,8-naphthalene diimide.
[0009] Surface modification of yttrium oxide powder using 1,8-naphthalene diimide can further improve the flexural strength of the ceramic core. The reason may be that surface modification of yttrium oxide powder using 1,8-naphthalene diimide slows down the rapid gelation of yttrium oxide powder and other components after combination, thereby improving the performance of the coating and further improving the flexural strength of the ceramic core.
[0010] As a further technical solution, the weight ratio of the yttrium oxide powder to 1,8-naphthalene diimide is 5~14:1.
[0011] When the weight ratio of yttrium oxide powder to 1,8-naphthalene diimide is 5-14:1, the bending strength of the ceramic core can be further improved.
[0012] As a further technical solution, the preparation method of the modified yttrium oxide powder includes the following steps: dissolving the 1,8-naphthalene diimide in xylene to obtain a 1,8-naphthalene diimide solution, adding the yttrium oxide powder to the 1,8-naphthalene diimide solution, dispersing evenly, concentrating, and drying to obtain the modified yttrium oxide powder.
[0013] As a further technical solution, the mass fraction of the 1,8-naphthalimide solution is 5% to 10%.
[0014] As a further technical solution, the raw material of the modified yttrium oxide powder also includes methyl MQ silicone resin.
[0015] In the process of using 1,8-naphthalene diimide to modify the surface of yttrium oxide powder, the inventors found that after adding methyl MQ silicone resin, 1,8-naphthalene diimide and methyl MQ silicone resin jointly modified the surface of yttrium oxide powder, which can further improve the bending strength of the ceramic core.
[0016] As a further technical solution, the weight ratio of the yttrium oxide powder, 1,8-naphthalene diimide and methyl MQ silicone resin is 25:(2.5~4):(1~2.5).
[0017] When the weight ratio of yttrium oxide powder, 1,8-naphthalene diimide and methyl MQ silicone resin is 25:(2.5~4):(1~2.5), the bending strength of the ceramic core can be further improved.
[0018] As a further technical solution, the preparation method of the modified yttrium oxide powder includes the following steps: dissolving the 1,8-naphthalene diimide and methyl MQ silicone resin in xylene to obtain a mixed solution, adding the yttrium oxide powder to the mixed solution, dispersing evenly, concentrating, and drying to obtain the modified yttrium oxide powder.
[0019] As a further technical solution, the mass fraction of the mixed solution is 10%~15%.
[0020] As a further technical solution, in step S2, the method for preparing the back layer shell comprises the following steps: applying a back layer coating on the surface layer shell, sprinkling sand, and drying to obtain a back layer shell.
[0021] As a further technical solution, the back layer coating comprises the following components in parts by weight: 20-30 parts of bauxite and 26-46 parts of silica sol.
[0022] As a further technical solution, when preparing the surface layer shell, the surface layer shell is prepared repeatedly for 2 times; when preparing the back layer shell, the back layer shell is prepared repeatedly for 8 times.
[0023] As a further technical solution, in the process of preparing the surface shell, yttrium oxide sand with a particle size of 15-74 μm is used for sand spreading.
[0024] As a further technical solution, during the preparation of the back layer shell, bauxite sand with a particle size of 15-74 μm is used for sand spreading.
[0025] As a further technical solution, in the process of preparing the back layer shell, no sand is sprinkled after the last application of the back layer coating.
[0026] As a further technical solution, during the dewaxing, the dewaxing temperature is 140-195° C. and the dewaxing time is 20-25 minutes.
[0027] As a further technical solution, in step S2, during the calcination, the temperature is 1025-1075°C and the calcination time is 2-4 hours.
[0028] The working principle and beneficial effects of the present invention are: In the present invention, a graphite and ceramic core composite titanium alloy casting process is adopted, the outer mold adopts a recyclable graphite mold, the inner core adopts a ceramic core prepared by a loss casting process, and the graphite mold and the ceramic core are combined, smelted, and cast to obtain a titanium alloy casting with good quality and a short production cycle. In the preparation process of the ceramic core, the binder in the surface coating includes dysprosium oxide, potassium silicate and silica sol. The combination of these three binders helps to effectively combine the components in the surface coating, thereby improving the creep resistance and bending strength of the ceramic core. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the following embodiments and comparative examples, the model of methyl MQ silicone resin is AM-8080; the particle size of yttrium oxide powder is 50 nm; the particle size of yttrium oxide sand is 43 μm; the particle size of bauxite is 38 μm; the particle size of bauxite sand is 74 μm; and the model of silica sol is AS-30.
[0031] Example 1 A graphite and ceramic core composite titanium alloy casting process includes the preparation of a graphite mold, the preparation of a ceramic core, the degassing of the graphite mold, the combination of the degassed graphite mold and the ceramic core, smelting, and casting. The preparation of the ceramic core includes the following steps: S1. Apply a surface coating on the wax mold. After the coating stops flowing, sprinkle yttrium oxide sand on the surface of the surface coating and dry it. Repeat the preparation of the surface shell twice. S2, coating the surface layer mold shell with a back layer coating, and after the coating stops flowing, sprinkling bauxite sand on the surface of the back layer coating, drying, and obtaining a back layer mold shell; repeating the preparation of the back layer mold shell 8 times, and after the last coating of the back layer coating, no bauxite sand is sprinkled; after preparing the back layer mold shell, dewaxing at 140° C. for 25 min, and calcining at 1025° C. for 4 h to obtain a ceramic core; The surface coating comprises the following components in parts by weight: 23 parts of yttrium oxide powder, 30 parts of a binder; The binder includes 7.5 parts of dysprosium oxide, 7.5 parts of potassium silicate and 15 parts of silica sol; The back layer coating comprises the following components in parts by weight: 20 parts of bauxite and 26 parts of silica sol.
[0032] Example 2 A graphite and ceramic core composite titanium alloy casting process includes the preparation of a graphite mold, the preparation of a ceramic core, the degassing of the graphite mold, the combination of the degassed graphite mold and the ceramic core, smelting, and casting. The preparation of the ceramic core includes the following steps: S1. Apply a surface coating on the wax mold. After the coating stops flowing, sprinkle yttrium oxide sand on the surface of the surface coating and dry it. Repeat the preparation of the surface shell twice. S2, coating the surface layer mold shell with a back layer coating, and after the coating stops flowing, sprinkling bauxite sand on the surface of the back layer coating, drying, and obtaining a back layer mold shell; repeating the preparation of the back layer mold shell 8 times, and after the last coating of the back layer coating, no bauxite sand is sprinkled; after preparing the back layer mold shell, dewaxing at 175° C. for 23 min, and calcining at 1050° C. for 4 h to obtain a ceramic core; The surface coating comprises the following components in parts by weight: 30 parts of yttrium oxide powder, 36 parts of a binder; The binder includes 9 parts of dysprosium oxide, 9 parts of potassium silicate and 18 parts of silica sol; The back layer coating comprises the following components in parts by weight: 25 parts of bauxite and 36 parts of silica sol.
[0033] Example 3 A graphite and ceramic core composite titanium alloy casting process includes the preparation of a graphite mold, the preparation of a ceramic core, the degassing of the graphite mold, the combination of the degassed graphite mold and the ceramic core, smelting, and casting. The preparation of the ceramic core includes the following steps: S1. Apply a surface coating on the wax mold. After the coating stops flowing, sprinkle yttrium oxide sand on the surface of the surface coating and dry it. Repeat the preparation of the surface shell twice. S2, coating the surface layer mold shell with a back layer coating, and after the coating stops flowing, sprinkling bauxite sand on the surface of the back layer coating, drying, and obtaining a back layer mold shell; repeating the preparation of the back layer mold shell 8 times, and after the last coating of the back layer coating, no bauxite sand is sprinkled; after preparing the back layer mold shell, dewaxing at 195° C. for 20 minutes, and calcining at 1075° C. for 2 hours to obtain a ceramic core; The surface coating comprises the following components in parts by weight: 35 parts of yttrium oxide powder, 50 parts of a binder; The binder includes 12.5 parts of dysprosium oxide, 12.5 parts of potassium silicate and 25 parts of silica sol; The back layer coating comprises the following components in parts by weight: 30 parts of bauxite and 46 parts of silica sol.
[0034] Example 4 The only difference between this embodiment and embodiment 2 is that in this embodiment, the binder includes 27 parts of dysprosium oxide, 3 parts of potassium silicate and 6 parts of silica sol.
[0035] Example 5 The only difference between this embodiment and embodiment 2 is that in this embodiment, the binder includes 24 parts of dysprosium oxide, 4 parts of potassium silicate and 8 parts of silica sol.
[0036] Example 6 The only difference between this embodiment and embodiment 2 is that in this embodiment, the binder includes 18 parts of dysprosium oxide, 6 parts of potassium silicate and 12 parts of silica sol.
[0037] Example 7 The only difference between this embodiment and Embodiment 6 is that in this embodiment, the yttrium oxide powder is a modified yttrium oxide powder, and the preparation method of the modified yttrium oxide powder comprises the following steps: dissolving 6 parts of 1,8-naphthalene diimide in xylene to obtain a 1,8-naphthalene diimide solution with a mass fraction of 6%, adding 24 parts of yttrium oxide powder to the 1,8-naphthalene diimide solution with a mass fraction of 6%, dispersing evenly, concentrating, and drying to obtain modified yttrium oxide powder.
[0038] Example 8 The only difference between this embodiment and embodiment 7 is that in this embodiment, 29 parts of yttrium oxide powder and 1 part of 1,8-naphthalene diimide are added.
[0039] Example 9 The only difference between this embodiment and embodiment 7 is that in this embodiment, 28 parts of yttrium oxide powder and 2 parts of 1,8-naphthalimide are added.
[0040] Example 10 The only difference between this embodiment and embodiment 7 is that, in this embodiment, 25 parts of yttrium oxide powder and 5 parts of 1,8-naphthalene diimide are added.
[0041] Embodiment 11 The only difference between this embodiment and Embodiment 10 is that, in this embodiment, the raw material of the modified yttrium oxide powder also includes methyl MQ silicone resin, and the preparation method of the modified yttrium oxide powder includes the following steps: dissolving 2 parts of 1,8-naphthalene diimide and 3 parts of methyl MQ silicone resin in xylene to obtain a mixed solution with a mass fraction of 10%, adding 25 parts of yttrium oxide powder to the mixed solution with a mass fraction of 10%, dispersing evenly, concentrating, and drying to obtain modified yttrium oxide powder.
[0042] Example 12 The only difference between this embodiment and embodiment 11 is that, in this embodiment, 25 parts of yttrium oxide powder, 4.5 parts of 1,8-naphthalimide, and 0.5 parts of methyl MQ silicone resin are added.
[0043] Example 13 The only difference between this embodiment and embodiment 11 is that, in this embodiment, 25 parts of yttrium oxide powder, 2.5 parts of 1,8-naphthalimide and 2.5 parts of methyl MQ silicone resin are added.
[0044] Embodiment 14 The only difference between this embodiment and embodiment 11 is that, in this embodiment, 25 parts of yttrium oxide powder, 4 parts of 1,8-naphthalimide and 1 part of methyl MQ silicone resin are added.
[0045] Comparative Example 1 The only difference between this comparative example and Example 1 is that in this comparative example, no dysprosium oxide is added to the binder, 15 parts of potassium silicate and 15 parts of silica sol are added.
[0046] Comparative Example 2 The difference between this comparative example and Example 1 is that in this comparative example, potassium silicate is not added to the binder, 15 parts of dysprosium oxide and 15 parts of silica sol are added.
[0047] Comparative Example 3 The only difference between this comparative example and Example 1 is that in this comparative example, no dysprosium oxide and potassium silicate are added to the binder, and 30 parts of silica sol are added.
[0048] Experimental Example 1 Creep Resistance The creep deformation of the ceramic cores prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was measured by using an RBX-1700 shell high temperature deformation instrument at a temperature range of 1520 to 1540° C. for 1 hour. The test results are shown in Table 1 below. Table 1 Test results
[0049] In Table 1, compared with Comparative Examples 1 to 3, the creep deformation of the ceramic core prepared in Example 1 is significantly reduced, indicating that the creep resistance of the ceramic core can be effectively improved by using three binders, dysprosium oxide, potassium silicate and silica sol, in the preparation process of the ceramic core. In addition, the creep deformation of the ceramic core prepared in Examples 1 to 3 is less than 0.1 mm, indicating that the ceramic core prepared in this solution has good creep resistance and can improve the overall quality of titanium alloy castings.
[0050] Experimental Example 2 Bending Strength Test The ceramic cores prepared in Examples 1 to 14 and Comparative Examples 1 to 3 were tested for room temperature flexural strength and high temperature flexural strength according to the test method in HB 5353.3-2004 "Test Methods for Performance of Investment Casting Ceramic Cores Part 3: Determination of Flexural Strength". When the high temperature flexural strength test was conducted, the test temperature was 1400°C, the holding time was 30 minutes, and each test value was measured 5 times to take the average value. The test results are shown in Table 2 below.
[0051] Table 2 Test results
[0052] In Table 2, compared with Comparative Examples 1 to 3, the room temperature flexural strength and high temperature flexural strength of the ceramic core prepared in Example 1 are significantly improved, indicating that in the preparation process of the ceramic core, when the binder in the surface coating includes dysprosium oxide, potassium silicate and silica sol, the flexural strength of the ceramic core can be effectively improved by using these three binders in combination. Compared with Examples 2 and 4, the room temperature flexural strength and high temperature flexural strength of the ceramic core prepared in Examples 5 to 6 are improved, indicating that when the weight ratio of dysprosium oxide, potassium silicate and silica sol is 3 to 6:1:2, the flexural strength of the ceramic core can be further improved. Compared with Example 6, the room temperature flexural strength and high temperature flexural strength of the ceramic core prepared in Examples 7 to 10 are improved, indicating that the surface modification of yttrium oxide powder using 1,8-naphthalene diimide can further improve the flexural strength of the ceramic core. Compared with Examples 7 to 8, the room temperature flexural strength and high temperature flexural strength of the ceramic core prepared in Examples 9 to 10 are improved, indicating that when the weight ratio of yttrium oxide powder to 1,8-naphthalene dicarboxylic acid imide is 5 to 14:1, the flexural strength of the ceramic core can be further improved. Compared with Example 10, the room temperature flexural strength and high temperature flexural strength of the ceramic core prepared in Examples 11 to 14 are improved, indicating that the flexural strength of the ceramic core can be further improved by using 1,8-naphthalene dicarboxylic acid imide and methyl MQ silicone resin to jointly modify the surface of yttrium oxide powder. In addition, compared with Examples 11 to 12, the room temperature flexural strength and high temperature flexural strength of the ceramic core prepared in Examples 13 to 14 are improved, indicating that when the weight ratio of yttrium oxide powder, 1,8-naphthalene dicarboxylic acid imide and methyl MQ silicone resin is 25: (2.5 to 4): (1 to 2.5), the flexural strength of the ceramic core can be further improved.
[0053] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A graphite and ceramic core composite titanium alloy casting process, comprising the preparation of a graphite mold, the preparation of a ceramic core, the degassing of the graphite mold, the combination of the degassed graphite mold and the ceramic core, smelting, and casting, characterized in that: The preparation of the ceramic core comprises the following steps: S1. preparing a surface shell on a wax mold; S2, preparing a back layer shell on the surface layer shell, dewaxing, and calcining to obtain a ceramic core; In step S1, the method for preparing the surface shell mold comprises the following steps: applying a surface coating on the wax mold, sprinkling sand, and drying to obtain a surface shell mold; The surface coating comprises the following components in parts by weight: 23-35 parts of yttrium oxide powder and 30-50 parts of a binder; The binder includes dysprosium oxide, potassium silicate and silica sol.
2. A graphite and ceramic core composite titanium alloy casting process according to claim 1, characterized in that: The weight ratio of the dysprosium oxide, potassium silicate and silica sol is 3-6:1:
2.
3. A graphite and ceramic core composite titanium alloy casting process according to claim 1, characterized in that: The yttrium oxide powder is modified yttrium oxide powder, and the raw materials of the modified yttrium oxide powder include yttrium oxide powder and 1,8-naphthalene diimide.
4. A graphite and ceramic core composite titanium alloy casting process according to claim 3, characterized in that: The weight ratio of the yttrium oxide powder to 1,8-naphthalene diimide is 5-14:
1.
5. A graphite and ceramic core composite titanium alloy casting process according to claim 3, characterized in that: The preparation method of the modified yttrium oxide powder comprises the following steps: dissolving the 1,8-naphthalene diimide in xylene to obtain a 1,8-naphthalene diimide solution, adding the yttrium oxide powder to the 1,8-naphthalene diimide solution, dispersing evenly, concentrating, and drying to obtain the modified yttrium oxide powder.
6. A graphite and ceramic core composite titanium alloy casting process according to claim 3, characterized in that: The raw materials of the modified yttrium oxide powder also include methyl MQ silicone resin.
7. A graphite and ceramic core composite titanium alloy casting process according to claim 6, characterized in that: The weight ratio of the yttrium oxide powder, 1,8-naphthalene diimide and methyl MQ silicone resin is 25:(2.5-4):(1-2.5).
8. A graphite and ceramic core composite titanium alloy casting process according to claim 1, characterized in that: In step S2, the method for preparing the back layer shell comprises the following steps: coating the back layer coating on the surface layer shell, sprinkling sand, and obtaining the back layer shell.
9. A graphite and ceramic core composite titanium alloy casting process according to claim 8, characterized in that: The back layer coating comprises the following components in parts by weight: 20-30 parts of bauxite and 26-46 parts of silica sol.
10. A graphite and ceramic core composite titanium alloy casting process according to claim 1, characterized in that: In step S2, during the calcination, the temperature is 1025-1075° C. and the calcination time is 2-4 hours.
Citation Information
Cited By
Preparation method of graphite and ceramic core composite cavity for titanium alloy casting based on 3D printing technology
CN120502666A
Preparation method of ceramic core for titanium alloy casting
CN121289409A
